Comparative spectroscopic, calorimetric, and computational studies of nucleic acid complexes with 2',5"-versus 3',5"-phosphodiester linkages. - Jin, R (1993)
We have used a combination of spectroscopic, calorimetric, and computational techniques to characterize the properties of nucleic acid complexes with 2',5''- and 3',5''-phosphodiester linkages. Specifically, we have compared the properties of complexes formed by the association of 3',5'' single-stranded 16-mers of adenylic acid (A16) and thymidylic acid (T16) with the complexes formed by the corresponding single-stranded 16-mers with 2',5''-phosphodiester linkages (A*16 and T*16). Our results reveal the following differential features: (i) the 3',5'' strands form either a duplex or a triplex, depending on the sodium ion concentration, whereas the 2',5'' strands form either a triplex or no complex at all; (ii) the 2',5'' and 3',5'' triplexes exhibit significantly different CD spectra, suggesting that the two triplex states are conformationally nonequivalent; (iii) the 2',5'' triplex has a lower charge density than the 3',5'' triplex; (iv) the thermal stability of the 3',5'' triplex, as expected, is concentration dependent, whereas the thermal stability of the 2',5'' triplex is concentration independent; (v) relative to their component single strands, the 2',5'' triplex is thermodynamically much less stable than the 3',5'' triplex, despite being thermally more stable; (vi) the reduced thermodynamic stability of the 2',5'' triplex relative to the 3',5'' triplex is overwhelmingly enthalpic in origin. In the aggregate, our results reveal and characterize significant differences in the properties of complexes formed by the association of strands with identical base sequences but different phosphodiester linkages. We describe a structural model that is consistent with many of the differential properties observed. We also speculate on how these differential properties may have provided an evolutionary advantage for 3',5'' linkages and how the properties of 2',5'' complexes might be exploited in antisense strategies.